PENYULUHAN PENERAPAN IPTEKS GUNA MEMPEROLEH STATUS HAK ATAS TANAH - Johan Rongalaha; James Y. Palenewen (JURNAL PENGABDIAN PAPUA, 2022)
This service was carried out with the title Application of Science and Technology to Obtain Land Rights Status in Nendali Village, East Sentani District, Jayapura Regency, which was carried out in Nendali village, activities carried out for partners due to cases from partners regarding the misunderstanding of the importance of land rights status in order to obtain legal certainty so that with the expertise possessed by the servant they can apply the science and technology. Methods The implementation of this service is carried out by applying science and technology through lectures and discussions which will be held on Saturday, July 31, 2021, which will be held at the village hall. Land Rights and Land Registration based on statutory regulations to obtain legal certainty. The output of this service is increasing partner knowledge regarding land rights and land registration in order to obtain legal certainty guarantees, and also complete land registration as pre-adjudication with the aim of making it easier for partners to complete land registration.Keywords: Application; science and technology; status; land rights